An Examination of the Challenges Faced in the Implementation of the Competence Based Curriculum in Secondary Schools in Uganda. - Kukundakwe, Ruth (Kabale University, 2024)
The study examined the challenges faced in the implementation of the competence-based curriculum in secondary schools in Uganda; A case study of Rukiga district following the objectives of the study which were to identify the methods used by secondary teachers in teaching the CBC, to examine the availability of materials (financial, library, physical, and instructional) used in competency-based curriculum in schools and to capture teachers’ suggestions for improvement. The study adopted descriptive research design using both qualitative and quantitative approaches. A sample of 302 respondents was used for the study and data collection tools were both interviews and questionnaires. The results of the study revealed that a significant portion of teachers (62%) incorporate PBL into their teaching. However, a noticeable percentage (28%) are either unsure or disagree with using this method, suggesting variability in adoption or possibly a lack of training or resources for effective implementation. The study concluded that secondary teachers employ a range of instructional methods to implement CBC, including Project-Based Learning, Inquiry-Based Learning, Collaborative Learning, the Flipped Classroom Model, and Differentiated Instruction. The majority of teachers recognize the benefits of these methods, though there is variability in their application. While Project-Based Learning, Inquiry-Based Learning, and Collaborative Learning are widely used, some teachers face challenges with the Flipped Classroom Model and Differentiated Instruction. The study recommended that there is a need for more targeted training and support to ensure consistent and effective use of these pedagogical approaches and government should allocate sufficient resources, including materials, technology, and infrastructure, to support the successful delivery of the CBC.